Facile and scalable preparation of 2D-MoS2/graphene oxide composite for supercapacitor - Yin, Xianglu; Teng, Aijun; Zeng, Zehua; Meng, Hong; Wu, Wei (Ionics, 2022)
Due to both hydrophilic oxygen–containing groups and hydrophobic unoxidized aromatic rings, graphene oxide (GO) exhibits amphiphilic properties, similar to common surfactants. Here, hydrophobic bulk molybdenum disulfide (MoS 2 ) was successfully exfoliated in GO aqueous dispersion under the condition of high shear force. The amphiphilic GO nanosheets play an importance role in exfoliation of bulk MoS 2 and inhibiting agglomeration of two-dimensional (2D) MoS 2 . The stacking supramolecular interaction and hydrophobic force enable rapid formation of 2D-MoS 2 /GO composite. Meanwhile, the strong electrostatic repulsion make composite uniformly dispersed in water. The exfoliation conditions were optimum that include pH value, exfoliation time, GO concentration, oxidation level of GO, and size of bulk MoS 2 . The average length and thickness of optimum 2D-MoS 2 nanosheets are 161.3 nm and below 10 nm, respectively. The contents of 2D-MoS 2 in composites are up to 4.87%. The structure characterization and quenched fluorescence also demonstrated that 2D-MoS 2 is adhered to the surface of GO and dispersing in water. The 2D-MoS 2 /rGO film prepared from prepared dispersion shows an outstanding volume specific capacitance and cycle stability in supercapacitor. Overall, this work provides a facile and scalable technology for preparing 2D-MoS 2 /GO composite without any additives, which can be used for supercapacitor electrode.